Small RNAs and development. - Yang, Z.; Wu, J. (Medical science monitor : international medical journal of experimental and clinical research, 2006)
Small RNAs, including microRNAs (miRNAs), short interfering RNAs (siRNAs), and siRNA-like scan RNAs (scnRNAs), are known to be crucial for regulatory functions in diverse species, with special focus on their interference in the development of plants as well as of C. elegans, Drosophila, and other animals. The functions of small RNAs on the complex regulatory network of metazoan embryonic development are presented in this article. In addition, indirect evidence is summarized here for those miRNAs which are important regulators controlling the biological processes of germ-cell development.